Superior Microwave Absorption Based on ZnO Capped MnO2 Nanostructures. Issue 15 (8th June 2020) - He, Gaihua; Duan, Yuping; Pang, Huifang; Hu, Jianjun
Abstract: Dielectric composites based on polybasic components with hierarchical structures have promising potentials for electromagnetic absorber. However, strategy to strengthen coupling of transition metal oxides still demands to be optimized to enhance electromagnetic loss. Herein, inspired by the hierarchical structure of balsam pear, ultrafine ZnO is uniformly distributed and tightly capped in MnO2 by self‐assembly hydrothermal method. The unique hierarchical structure provides abundant polarization centers with large specific surface area. The compositions promote attenuation performance of electromagnetic waves, enhance relative permittivity and satisfy impedance matching as compared with that of pure ZnO or MnO2 . The effective bandwidth (RL< −10 dB) reaches 5.93 GHz obtained with thin thickness of 1.8 mm. The effective bandwidth reaches 15 GHz via regulating their thickness. The fabricated MnO2 /ZnO composites can achieve great adaptability in microwave. MnO2 /ZnO composites keep stability even heated 700 °C in air. The phase and weight remain unchanged. The proposed interfacial modulation strategy can provide new opportunities for the design of efficient electromagnetic absorber with thermal stability. Abstract : The unique hierarchical structure with ultrafine ZnO nanocrystal tightly capped MnO2 provides abundant polarization centers on its surface with large specific surface area. Compared with pure ZnO and MnO2, the compositions achieve superior microwave absorption with good thermal stability via synergetic effect, which attributes to enhanced dielectric loss and optimized impedance matching.